Layer‐Dependent Raman Spectroscopy and Electronic Applications of Wide‐Bandgap 2D Semiconductor β‐ZrNCl. Issue 14 (20th February 2022) - Nong, Huiyu; Wu, Qinke; Tan, Junyang; Sun, Yujie; Zheng, Rongxu; Zhang, Rongjie; Zhao, Shilong; Liu, Bilu
Abstract: In recent years, 2D layered semiconductors have received much attention for their potential in next‐generation electronics and optoelectronics. Wide‐bandgap 2D semiconductors are especially important in the blue and ultraviolet wavelength region, although there are very few 2D materials in this region. Here, monolayer β‐type zirconium nitride chloride (β‐ZrNCl) is isolated for the first time, which is an air‐stable layered material with a bandgap of ≈3.0 eV in bulk. Systematical investigation of layer‐dependent Raman scattering of ZrNCl from monolayer, bilayer, to bulk reveals a blueshift of its out‐of‐plane A 1g peak at ≈189 cm –1 . Importantly, this A 1g peak is absent in the monolayer, suggesting that it is a fingerprint to quickly identify the monolayer and for the thickness determination of 2D ZrNCl. The back gate field‐effect transistor based on few‐layer ZrNCl shows a high on/off ratio of 10 8 . These results suggest the potential of 2D β‐ZrNCl for electronic applications. Abstract : This work is about fundamental Raman spectroscopy and transistor applications of a wide‐bandgap and air‐stable 2D β‐type zirconium nitride chloride (β‐ZrNCl). Systematical investigation of layer‐dependent Raman scattering of the 2D β‐ZrNCl from monolayer to bulk reveals a blueshift of its out‐of‐plane A 1g peak at ≈189 cm ‐1 . The back gate field‐effect transistor shows a high on/off ratio, suggesting the potential for electronic applications.